Assessing student perceptions on hybrid learning - Zuraida Alwadood; Suhaila Ab Halim; Sumarni Abu Bakar; Norlenda Mohd Noor (Institute of Advanced Engineering and Science, 2023)
COVID-19 has put a large impact on the education system all around the world. School, college and university students are forced to attend hybrid learning (HL) classes. This has posed challenges to the learners to adapt with the new learning system. The objective of this case study is to examine students’ perception on HL, in particular, the impacts on students’ learning experience. This study used survey as the methodology and the instrument for data collection is questionnaire. Data was collected from 93 students of five mathematics classes at Universiti Teknologi MARA (UiTM), Malaysia. Their perceptions in five learning aspects were analyzed, namely the accessibility to the online learning system, the effectiveness of both HL and face-to-face (f2f) learning, the pedagogical, technical and social aspects. The results have shown positive acceptance on HL and they enjoyed the new learning experience which uses both f2f and online mediums. This finding indicated that HL has a good potential to be extended to other courses at the university. This also indicated the opportunity for the university to enhance the teaching and learning methods and support the HL system in terms of moral and physical assistances.